Herpes Simplex Virus 2-Induced Acute Retinal Necrosis in an Immunocompetent Young Adult: A Diagnostic Conundrum - Vipin Rana; Amit Nandan Tripathi; Nidhi Kalra; N. Madhu; Sudhir Dubey; Sandeepan Bandopadhyay (Delhi Journal of Ophthalmology, 2025)
The purpose of this retrospective case report study was to report a case of young immunocompetent male with herpes simplex virus-induced (HSV) acute retinal necrosis (ARN) with initial diagnosis of unilateral disc swelling. A 32-year-old male with no significant medical history presented with blurred vision, periorbital pain, and redness in the left eye. Initial diagnosis of the left optic neuritis led to treatment with high-dose corticosteroids. Subsequent examination revealed circumferential tongue-shaped lesions in the peripheral retina in both the eyes, leading to the diagnosis of bilateral ARN. Aqueous humor analysis confirmed HSV-2 infection. Treatment with oral valacyclovir and oral steroids was initiated. However, the patient developed left eye retinal detachment, requiring surgery. Prophylactic laser photocoagulation was performed in the right eye to prevent detachment. Postoperative improvements included retinitis lesion healing and vision restoration to 6/36 in the left eye. Close monitoring and detailed dilated fundus examination, including the peripheral retina, are crucial for patients with disc swelling of unclear cause to rule out ARN.